Mercury contents in aquatic macrophytes from two reservoirs in the Paraíba do Sul: Guandú river system, SE Brazil - Molisani,M. M. (2006)
This paper reports on a study to determine the Hg content in the five most abundant aquatic macrophyte species (Elodea densa, Sagittaria montevidensis, Salvinia auriculata, Pistia stratiotes and Eichhornia crassipes) in two artificial reservoirs flooded by water diverted from the Paraíba do Sul river, SE Brazil. The potential of these species for Hg accumulation and their role in Hg transport along the river system due to macrophyte management were evaluated. Mercury concentrations were higher in free-floating than in rooted species. Roots were also richer in Hg than were leaves. Dry weight Hg concentrations in leaves and roots from all species varied from 46-246 ng.g-1 to 37-314 ng.g-1, respectively. These values are higher than those reported for uncontaminated lakes in Brazil and in other tropical areas and similar to those reported for moderately contaminated sites. Mercury concentrations can be attributed to fluvial transport from the heavily industrialized Paraíba do Sul river basin. Intensive sampling of Pistia stratiotes from two sites in the Vigário reservoir was performed to evaluate the capacity of Hg incorporation in short periods of time. The results showed a significant negative correlation between Hg content and size class of individual plants, demonstrating the importance of juveniles, fast growing plants in absorbing Hg. The foremost impact related to Hg contents in the studied area concerns the periodic removal of macrophytes for reservoir management, followed by disposal in nearby areas. This results in the mobilization of 0.52 to 1.3 Kg of Hg per year, a significant fraction of the Hg burden present in reservoir waters. Disposal of such material may result in Hg leaching to river systems, affecting the Hg transfer throughout the basin.